Computerised dynamic posturography for postural control assessment in subjects wearing multifocal contact lenses dedicated for myopia control. (1st May 2021) - Przekoracka, Katarzyna; Michalak, Krzysztof Piotr; Olszewski, Jan; Michalski, Andrzej; Przekoracka‐Krawczyk, Anna
Abstract: Purpose: To measure body balance using computerised dynamic posturography in young adults wearing multifocal contact lenses (MFCL) with high addition powers designed for myopia control. Methods: Twenty‐four young adults (mean age: 24 years) wearing distance‐centred soft MFCL (SwissLens Orbis Relax) with two different central zones (3 and 4.5 mm), two addition powers (+2 D, +4 D) and single vision control lenses. Body balance was measured on a moving platform under three viewing conditions: (1) eyes open when fixating on letters at 3 m or (2) at 40 cm, as well as (3) with the eyes closed. Parameters of body stabilisation were analysed: the rate of body stabilisation (τrelax ), the stabilisation time (Tmax ) and the number of oscillations (Nosc ). Results: The MFCLs did not produce a significant difference in the mean values of the analysed parameters ( p  > 0.05 for τrelax, Tmax, Nosc ). However, a positive correlation was found between pupil size and Nosc and Tmax ( p  < 0.01), suggesting an effect of the +4 D add with the 3 mm central zone on the posturographic parameters. As was expected, dynamic body stabilisation was better with eyes open versus eyes closed ( p  < 0.005). Conclusions: Distance‐centred MFCLs with a medium addition (+2 D) do not disturb body stabilisation in young adults. However, high additions (+4 D) with a small central zone may affect body balance control in subjects with large pupil size.